Strengthening Ecotourism to Improve Quality of Life in Ubung Kaja Village through Creativity, Order, and Cultural Values - JAYAWARSA, A. A Ketut; SAPUTRA, Komang Adi Kurniawan; NARINDRA, Ngurah Mayun (PT Batara Swastika Harati, 2024)
This KKN-PPM (Student Community Service) program was conducted in Ubung Kaja Village, North Denpasar District, Denpasar City, from July 22 to August 24, 2024, with the theme